SIV replication in human cells - Takeuchi, Hiroaki; Sakuma, Ryuta (Frontiers in Microbiology, 2012)
Current human immunodeficiency virus type 1 (HIV-1) pandemic is believed to originate from cross-species transmission of simian immunodeficiency virus (SIV) into human population. Such cross-species transmission, however, is not efficient in general, because viral replication is modulated by host cell factors, with the species specificity of these factors affecting viral tropism. An understanding of those host cell factors that affect viral replication contributes to elucidation of the mechanism for determination of viral tropism. This review will focus an anti-viral effect of ApoB mRNA editing catalytic subunit (APOBEC), tripartite motif protein 5 alpha (TRIM5α) and cyclophilins (Cyps) on SIV replication and provide insight into the mechanism of species-specific barriers against viral infection in human cells. It will then present our current understanding of the mechanism that may explain zoonotic transmission of retroviruses.